Nearly free silanols drive the interaction of crystalline silica polymorphs with membranes: Implications for mineral toxicity - Pavan, Cristina; Escolano-Casado, Guillermo; Bellomo, Chiara; Cananà, Stefania; Tomatis, Maura; Leinardi, Riccardo; Mino, Lorenzo; Turci, Francesco (Frontiers in Chemistry, 2023)
Crystalline silica (CS) is a well-known hazardous material that causes severe diseases including silicosis, lung cancer, and autoimmune diseases. However, the hazard associated to crystalline silica is extremely variable and depends on some specific characteristics, including crystal structure and surface chemistry. The crystalline silica polymorphs share the SiO2 stoichiometry and differentiate for crystal structure. The different crystal lattices in turn expose differently ordered hydroxyl groups at the crystal surface, i.e., the silanols. The nearly free silanols (NFS), a specific population of weakly interacting silanols, have been recently advanced as the key surface feature that governs recognition mechanisms between quartz and cell membrane, initiating toxicity. We showed here that the nearly free silanols occur on the other crystalline silica polymorphs and take part in the molecular interactions with biomembranes. A set of crystalline silica polymorphs, including quartz, cristobalite, tridymite, coesite, and stishovite, was physico-chemically characterized and the membranolytic activity was assessed using red blood cells as model membranes. Infrared spectroscopy in highly controlled conditions was used to profile the surface silanol topochemistry and the occurrence of surface nearly free silanols on crystalline silica polymorphs. All crystalline silica polymorphs, but stishovite were membranolytic. Notably, pristine stishovite did not exhibited surface nearly free silanols. The topochemistry of surface silanols was modulated by thermal treatments, and we showed that the occurrence of nearly free silanols paralleled the membranolytic activity for the crystalline silica polymorphs. These results provide a comprehensive understanding of the structure-activity relationship between nearly free silanols and membranolytic activity of crystalline silica polymorphs, offering a possible clue for interpreting the molecular mechanisms associated with silica hazard and bio-minero-chemical interfacial phenomena, including prebiotic chemistry.